Where would acute care nurses prefer to receive end-of-life care? a cross-sectional survey. (September 2020) - Shepherd, Jan; Waller, Amy; Sanson-Fisher, Rob; Clark, Katherine; Ball, Jean
Abstract: Background: Hospital-based nurses can offer a unique perspective about factors that can contribute to a good end-of-life experience, including the location in which end-of-life care is delivered. Objectives: To examine in a sample of hospital-based nurses, the location in which they personally would most and least prefer to be cared for at the end of life, and the reasons for these preferences. Design: Questionnaire-based, cross-sectional study. Setting and participants: 170 registered and enrolled nurses employed in acute care wards of three metropolitan hospitals in Australia between April 2016 and February 2017. Results: Nurses would most prefer to be cared for at home (53%) or in a hospice/palliative care unit (41%) at the end-of-life. Being in a familiar environment and feeling like dying is a more normal process were the main reasons reported for choosing these settings. The main reasons given by nurses for choosing a hospice/palliative care unit were that being cared for at home may place a burden on family/friends and hinder appropriate symptom management. Nurses would least prefer being cared for in an emergency department (49%) due to a perceived lack of privacy and adverse impact on the family; and residential aged care facilities (25%) due to perceived suboptimal symptom management and reduced likelihood of wishes being respected. Conclusion: Nurses in this study value familiarity of environment and normalising the dying process. The majority do not wish to burden their family and friends at the end of their lives. Important next steps in providing services that meet the needs of people facing the end of their lives include understanding how nurses' personal views may influence decision-making conversations with patients and families about location of care at the end-of-life, as well as determining the capacity of available services to meet patient and family needs.